The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/iai.72.3.1568-1579.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate Cyclase Toxin fromBordetella pertussisSynergizes with Lipopolysaccharide To Promote Innate Interleukin-10 Production and Enhances the Induction of Th2 and Regulatory T Cells

Abstract: Adenylate cyclase toxin (CyaA) from Bordetella pertussis can subvert host immune responses allowing bacterial colonization. Here we have examined its adjuvant and immunomodulatory properties and the possible contribution of lipopolysaccharide (LPS), known to be present in purified CyaA preparations. CyaA enhanced antigen-specific interleukin-5 (IL-5) and IL-10 production and immunoglobulin G1 antibodies to coadministered antigen in vivo. Antigen-specific CD4+-T-cell clones generated from mice immunized with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
108
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 57 publications
(60 reference statements)
11
108
2
Order By: Relevance
“…We and others have previously shown that CyaA of B. pertussis is an effective vaccine adjuvant in vivo, enhancing Ab responses to coadministered Ags (7)(8)(9)(10). Our studies also demonstrated that CyaA promotes Th2 and type 1 regulatory T (Tr1) cell responses to coadministered Ags (9).…”
supporting
confidence: 60%
See 4 more Smart Citations
“…We and others have previously shown that CyaA of B. pertussis is an effective vaccine adjuvant in vivo, enhancing Ab responses to coadministered Ags (7)(8)(9)(10). Our studies also demonstrated that CyaA promotes Th2 and type 1 regulatory T (Tr1) cell responses to coadministered Ags (9).…”
supporting
confidence: 60%
“…Our studies also demonstrated that CyaA promotes Th2 and type 1 regulatory T (Tr1) cell responses to coadministered Ags (9). Studies with innate immune cells in vitro indicated that these adaptive immune responses were mediated via the modulation of DC and macrophage activation.…”
mentioning
confidence: 69%
See 3 more Smart Citations